2022
DOI: 10.1136/bmjopen-2021-055415
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with accessing and utilisation of healthcare and provision of health services for residents of slums in low and middle-income countries: a scoping review of recent literature

Abstract: ObjectiveTo identify factors associated with accessing and utilisation of healthcare and provision of health services in slums.DesignA scoping review incorporating a conceptual framework for configuring reported factors.Data sourcesMEDLINE, Embase, CINAHL, Web of Science and the Cochrane Library were searched from their inception to December 2021 using slum-related terms.Eligibility criteriaEmpirical studies of all designs reporting relevant factors in slums in low and middle-income countries.Data extraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…We identified several factors that are particularly pertinent in slum settings, such as difficulty in dietary adherence, adherence medication, 15–18,26 lifestyle changes/behavior, 15,16,18,22,23,26 literacy and knowledge about the disease and diet, 14,15,17–19,26,30,35 costs and financial issues, 14,17–19,21–25,27,29,35 family/social/friends support, 14,25,26,29 availability/accessibility of healthcare services, the costs of health services, 15,17–20,23 patients‐providers interaction 14,24,25,29,30 . In line with our study, a previous scoping review suggested that factors such as knowledge, perception (including misconception and distrust), financial issues, stigma, healthcare needs and health services, competing priorities and inadequacy of social support, and so on, in the existing health system all contribute to the challenges faced by slum‐dwellers 39 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We identified several factors that are particularly pertinent in slum settings, such as difficulty in dietary adherence, adherence medication, 15–18,26 lifestyle changes/behavior, 15,16,18,22,23,26 literacy and knowledge about the disease and diet, 14,15,17–19,26,30,35 costs and financial issues, 14,17–19,21–25,27,29,35 family/social/friends support, 14,25,26,29 availability/accessibility of healthcare services, the costs of health services, 15,17–20,23 patients‐providers interaction 14,24,25,29,30 . In line with our study, a previous scoping review suggested that factors such as knowledge, perception (including misconception and distrust), financial issues, stigma, healthcare needs and health services, competing priorities and inadequacy of social support, and so on, in the existing health system all contribute to the challenges faced by slum‐dwellers 39 …”
Section: Discussionsupporting
confidence: 87%
“…14,24,25,29,30 In line with our study, a previous scoping review suggested that factors such as knowledge, perception (including misconception and distrust), financial issues, stigma, healthcare needs and health services, competing priorities and inadequacy of social support, and so on, in the existing health system all contribute to the challenges faced by slum-dwellers. 39 Costs and financial issues were frequently reported in studies as factors affecting healthcare-seeking behaviors, disease management, and also as a barrier to dietary adherence and eating healthy food, adherence to medication, and diabetes self-management. 14,[17][18][19][21][22][23][24][25]27,29,35 These barriers were also reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a commonly held assumption that the health conditions of urban populations are superior to their rural counterparts due to greater healthcare availability and economic opportunities [ 9 , 10 ]. Evidence from urban poor communities across Asia and Africa, however, show that poor and marginalized urban populations have worse access to ANC and facility childbirth compared to the non-poor, and often have maternal, newborn, and child mortality rates as high as or higher than those in rural areas [ 7 , 10 14 ]. In Kampala slums, for example, the estimated stillbirth rate is 43 deaths per 1000 live births which is more than double the 19 deaths per 1000 live births in rural areas of the country.…”
Section: Introductionmentioning
confidence: 99%
“…In Kijumo Village, Uganda, a rural community characterized by limited resources and infrastructure, accessing timely and quality maternal and child healthcare services poses significant challenges for many residents [21][22][23][24]. Limited financial resources, inadequate transportation infrastructure, and cultural norms that prioritize traditional healing practices may deter mothers from seeking essential healthcare services during pregnancy, childbirth, and the postnatal period [25][26]. Consequently, preventable maternal and infant deaths continue to occur, highlighting the urgent need for targeted interventions to address existing disparities and improve health outcomes in the community [27][28][29][30].…”
mentioning
confidence: 99%